Student financial assistance services - Advincula, Reynold; Mercado, Anne Katharine; Ortega, Myra Mae.; Rezaga, Michael Allan; Tambasin, Ferdinand (2002.)
Summary - SFAS is a service-oriented business enterprise, which caters to the needs of the CM students of the UP Visayas. It is to promote the sense of investing money without the need to have a big capital. Putting up a business such as SFAS requires a lot of effort, in depth and comprehensive study. The set-up is so complicated that a thorough seminar about credit cooperative is a necessity for each general manger. The "know-how" is very essential especially in presenting the financial statements. Although by nature, SFAS is a profit-oriented business, it should maintain itss quality of service to the students. After conducting a survey for at least 150 respondents, that is estimated to be 14% of the CM student population, the proponents got a majority of NO answers in putting up such business. Yet the proponents decided to take such reactions as a challenege, considering that the remaining 86% have not yet responded. SFAS does not require a big amount of capital for it to purse its goals. Nor does it need a building for the business to start. SFAS, as a business and for it flourish requires skills, knowledge, honest personnel, firm internal control, and a well planned marketing strategy.
Business Plan (Mgt 138 - Entrepreneurship) -- Iloilo City : University of the Philippines in the Visayas - College of Management, 2002.